How perceived Australian sexual norms shape sexual practices of East Asian and sub-Saharan African international students in Sydney - Sylvester R. Okeke (BMC, 2021)
Abstract Introduction Sexual norms, real or perceived, shape young people's sexual behaviour and may constitute one of the greatest challenges in HIV/STIs prevention among this population. This study used sexual script theory to explore how international students in Sydney, Australia - from traditional cultures of East Asian and sub-Saharan African countries - construct home backgrounds and Australian sexual norms and how this may shape their sexual practices during their studies in Australia. Methods The study involved face-to-face and telephone semi-structured in-depth interviews. Data were provided by 20 international students who are enrolled in various universities in Sydney. Interviews were audio-recorded, transcribed, coded into NVivo and analysed using reflexive thematic analysis. Results Identified patterns in the data showed three themes through which participants perceive sexual norms in Australia as distinctly different from their home country norms. First, participants stated that unlike their home country norms, sexual norms in Australia are permissive. Second, participants hold the view that compared to their home country norms, sex in Australia is largely casual as it is not always attached to love. Some participants revealed that this could shape their own sexual practices during their studies in Australia. Finally, participants noted that compared to their home countries' norm of sex talk taboo, Australia has an open sexual communication norm; which they believe, enables young people in western societies to easily acquire sexual health information. Conclusions Findings provide evidence to support a need for contextualized and effective sexual health services for international students that take account of perceptions around sexual norms and how they can be modified to ensure that sexual practices which these students may engage in, will be managed in a safe and responsible manner.